2017
DOI: 10.5213/inj.1732704.352
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Upper Urinary Tract Involvement in Patients With Ketamine-Associated Uropathy

Abstract: PurposeThe aims of this study were to investigate the prevalence of upper tract involvement in ketamine-associated uropathy, and to determine the predictors of hydronephrosis in patients with a history of ketamine abuse. MethodsThis was a cross-sectional study of a prospective cohort of patients with ketamine-associated uropathy. Data including demographics, pattern of ketamine abuse, pelvic pain and urgency or frequency (PUF) symptom score, uroflowmetry (UFM) parameters, serum renal function, and liver functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
(24 reference statements)
3
19
0
Order By: Relevance
“…This study revealed that elevated cholestatic liver enzyme levels correlated with the degree of ketamine-associated uropathy in these chronic ketamine abusers; this finding agrees with that of a previous study [ 22 ]. In 2009, Wong et al first identified ketamine-associated hepatobiliary tract complications [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study revealed that elevated cholestatic liver enzyme levels correlated with the degree of ketamine-associated uropathy in these chronic ketamine abusers; this finding agrees with that of a previous study [ 22 ]. In 2009, Wong et al first identified ketamine-associated hepatobiliary tract complications [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Since hydronephrosis appears to be involved later and less frequently, the secondary theory has been more accepted. A previous study showed that decreased functional bladder capacity was a risk factor of hydronephrosis development in chronic ketamine abusers, the result of which supports the secondary theory indirectly [ 22 ]. On this basis, some experts suggest that ketamine cystitis and ketamine hydronephrosis are characteristics of different clinical staging of ketamine-associated uropathy.…”
Section: Discussionmentioning
confidence: 67%
“…As well as bladder involvement, upper-urinary tract pathology presenting as hydronephrosis and flank pain has also been reported (Fig 2). A study by Yee et al 9 of 572 patients with ketamine-related LUTS found that up to 16.8% (n=96) of patients had hydronephrosis according to ultrasonography. Hydronephrosis was frequently accompanied by ureteral lesions, ureteral wall thickening, or vesicoureteral (vesicoureteric) reflux.…”
Section: Urological Complicationsmentioning
confidence: 99%
“…The incidence of upper urinary tract involvement varies in the literature, ranging from 6% to 63% of the reported series 3,4,14,70‐72 . Almost half of the patients with severe cystitis (mucosal disruption, with or without bleeding) have bilateral upper urinary tract involvement, but there is usually no correlation with LUTS severity, dose, and frequency of ketamine abuse 70,71 .…”
Section: Evidencementioning
confidence: 99%
“…Almost half of the patients with severe cystitis (mucosal disruption, with or without bleeding) have bilateral upper urinary tract involvement, but there is usually no correlation with LUTS severity, dose, and frequency of ketamine abuse 70,71 . Older age, abnormal serum enzyme profile, low bladder capacity, and high creatinine are predictors of hydronephrosis 72 …”
Section: Evidencementioning
confidence: 99%